Penguatan Manajemen Pengelolaan Spesimen Darah pada Petugas ATLM dan Perawat di Puskesmas Denpasar Utara - Cahyani, Anak Agung Ayu Eka; Jayanti, Desak Made Ari Dwi; Sintari, Silvia Ni Nyoman; Wahyudi, Hendro; Dharma, I Dewa Gede Candra (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Laboratory tests must be carried out according to existing procedures, so that accurate, fast and reliable results are obtained. Pre-analytical stage errors contribute the most to laboratory errors, namely 61%. Community Service activities for Medical Laboratory Technologists (ATLM) aim to provide understanding and reinforcement regarding blood specimen management. The targets of this activity are ATLM and nurses working at UPTD Puskesmas I North Denpasar, UPTD Puskesmas II North Denpasar, UPTD Puskesmas III North Denpasar as many as 20 people. This community service activity was carried out in June 2023. Measurement of the level of knowledge about blood specimen management using the questionnaire method. Counselling on blood specimen management was carried out by speakers from DPW PATELKI BALI and TLM Lecturers related to research in the field of management. The level of knowledge at the pre-analytical stage is in the Good category with a score of 86.92%. In the management of blood specimens, especially handling samples before examination, there appears to be a downward trend in the number of errors in the number of samples that are lysed, lacking and clotted.